15-3(2x-9)+x=115

Simple and best practice solution for 15-3(2x-9)+x=115 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-3(2x-9)+x=115 equation:


Simplifying
15 + -3(2x + -9) + x = 115

Reorder the terms:
15 + -3(-9 + 2x) + x = 115
15 + (-9 * -3 + 2x * -3) + x = 115
15 + (27 + -6x) + x = 115

Combine like terms: 15 + 27 = 42
42 + -6x + x = 115

Combine like terms: -6x + x = -5x
42 + -5x = 115

Solving
42 + -5x = 115

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -5x = 115 + -42

Combine like terms: 42 + -42 = 0
0 + -5x = 115 + -42
-5x = 115 + -42

Combine like terms: 115 + -42 = 73
-5x = 73

Divide each side by '-5'.
x = -14.6

Simplifying
x = -14.6

See similar equations:

| -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 | | 3x+60=10x+11 | | 23=-7(6v+7)+5(1-5v) | | 1.9/250=x/650 | | y-18=21 | | 4(2r+12)=6(4r-32) | | -5n+12=7n | | x^4+x^3-19x^2+x-20=0 | | -16x^2+80x+20=20 | | -248=c-253 | | 105=-5(7-7r) |

Equations solver categories